Dysfunction of the Glymphatic System Might Be Related to Iron Deposition in the Normal Aging Brain - Zhou, Wei; Shen, Bo; Shen, Wei-qiang; Chen, Hao; Zheng, Yi-feng; Fei, Jing-jing (Frontiers in Aging Neuroscience, 2020)
Objective: The study aims to detect the potential relationship between iron deposition and the function of the glymphatic system in the normal aging brain. Methods: We recruited 213 healthy participants. We evaluated the function of the glymphatic system using the index for diffusivity along the perivascular space (ALPS-index), assessed iron deposition on quantitative susceptibility mapping (QSM), and analyzed their relationship. Results: The mean age of participants was 60.1 ± 7.3, and 107 (50.2%) were female. The mean ALPS-index was 1.4 ± 0.2. The QSM values of the caudate nucleus, putamen, globus pallidus, thalamus, red nucleus, substantia nigra, and dentate nucleus were all related to the ALPS-index (all P < 0.001). Conclusions: The main finding of the current study is that the regional brain iron deposition was related to the function of the glymphatic system. Advances in knowledge: We first evaluated the relationship between deposition of brain iron and the dysfunction of the glymphatic system.